A Chinese town's get-rich scheme e-trash to cash. - Lin-Liu, J. (IEEE spectrum)
The electronic trash that most Americans deposit at center for recycling toxic materials often ends up polluting towns in developing countries. China has become the favored destination for the world's discarded computers and peripherals and the main source of used computer parts. In 2002, China banned the import of many used electronic items due to the electronic waste and hazardous waste it's causing. However, implementing the ban has been difficult because the shipment have created jobs for the underclass. China's import of electronic trash has given birth to towns whose economies are completely dependent on the trade. The trade might be easier to stamp out if it weren't actually improving the town's economy.